New Insights into the Role of Cellular Senescence and Its Therapeutic Implications in Ocular Diseases - Junying Wu; Xiuxing Liu; Yidan Liu; Wenru Su; Yehong Zhuo (Bioengineering)
The process of aging exerts profound effects on various physiological systems, leading to the progression of chronic degenerative disorders and pathologies associated with advancing age. Cellular senescence plays a central role in the aging process and the onset of various eye conditions associated with advancing age, including age-related macular degeneration (AMD), diabetic retinopathy (DR), glaucoma, cataracts, and ocular surface disorders. The accumulation of senescent cells (SnCs) and their secretion of pro-inflammatory and tissue-remodeling factors, collectively known as the senescence-associated secretory phenotype (SASP), exacerbate chronic inflammation, oxidative stress, and tissue dysfunction, contributing to disease progression. This study is the first to systematically integrate the multifaceted mechanisms of cellular senescence in ocular diseases, revealing differential regulatory mechanisms of specific signaling pathways across different ocular pathologies, thereby providing novel insights into the pathogenesis of these disorders. SnC-targeted therapies such as senolytics, senomorphics, SASP modulators, mitochondrial-targeted antioxidants, and epigenetic reprogramming are emerging as regenerative therapies, demonstrating potent anti-inflammatory effects, restoration of normal tissue physiology, and successful regeneration of ocular defects in preclinical models and clinical trials, while slowing senescence-associated disease progression. This review not only summarizes the role of cellular senescence in ocular diseases but also delves into potential therapeutic strategies, particularly highlighting novel perspectives for root-cause-targeted therapies from the unique angle of senescence biology, which may pioneer new directions for the treatment of ocular pathologies.